Political implications of the Indonesia-Singapore extradition agreement from a dauliyah perspective - Nazwan, Fauqi Muhtaromun; Saebani, Beni Ahmad; Alamsyah, Taufiq (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2025)
This study aims to analyze the political implications of the 2022 Indonesia–Singapore Extradition Treaty from the perspective of Siyasah Dauliyah, focusing on its linkage to the Defense Cooperation Agreement (DCA) and the Flight Information Region (FIR) arrangement. Employing a normative juridical method with a descriptive-analytical approach, the research examines primary and secondary legal sources, including Abdul Karim Zaidan’s Islamic extradition theory and Wahbah az-Zuhaili’s concept of territorial sovereignty. The findings indicate that the treaty holds strategic value for cross-border law enforcement, particularly through its retroactive clause, enabling the pursuit of corruption fugitives in Singapore. However, the bundling of the extradition agreement with the DCA and FIR raises sovereignty concerns that contradict key principles of Siyasah Dauliyah. The study concludes that the treaty’s effectiveness depends on sustained political commitment, harmonized legal procedures, and strengthened asset recovery mechanisms. The research contributes by integrating Islamic legal perspectives with modern international relations theory, offering a normative and practical framework for evaluating similar international agreements in the future.